The natural anti-tubercular agents: In silico study of physicochemical, pharmacokinetic and toxicological properties - Mohammad Firoz Khan, Md. Abdul Bari, Md. Kamrul Islam, Md. Shariful Islam, Md. Shahidulla Kayser, Nusrat Nahar, Md. Al Faruk, Mohammad A. Rashid (Journal of Applied Pharmaceutical Science, 2017)
The purpose of the present study is to explore the physicochemical, pharmacokinetic and toxicological properties and to correlate the calculated physicochemical properties with the absorption and distribution profile of seven natural anti-tubercular agents such as 6a,7-dehydro-N-formylnornantenine (DNF), Aristololactam (AL), Isoambreinolide (IA), Andrographolide (AGD), 8,8'-Biplumbagin (BPG), Plumericin (PC) and Tiliacorine (TC). The physicochemical properties such as intrinsic solubility (solubility of unionized form) in water (logS), partition coefficient (logP), H bond donor and acceptor count were calculated using MarvinSketch software. The pharmacokinetic and toxicological properties were calculated using online server PreADMET. The calculated aqueous solubility demonstrated that all the seven compounds possess limited solubility which ranged from very slightly soluble to practically insoluble. The calculation of partition coefficient suggested that all the compounds are lipophilic in nature and have higher affinity to reside in n-octanol than in water. The human intestinal absorption (HIA), Caco-2 cell penetrability, plasma protein binding (PPB) and Cbrain/Cblood of the seven compounds were ranged from 94.89% - 100.00%, 20.18 - 54.75 nm/s, 73.52% - 100.00% and 0.353 - 2.331, respectively. The computed metabolism demonstrated that DNF, AL, IA, PC and TC are substrate for cytochrome P450 3A4. However, all the compounds displayed inhibitory characteristics against cytochrome P450 3A4. The virtual screening also demonstrated that AL, PG and BPG are 2C19 inhibitors and all the natural agents except DNF are 2C9 inhibitors. In phase II reaction, IA, PG and DNF, AL, PG, BPG are the substrates for UDP-glucuronosyltransferase (UGT) and sulfotransferase (SULT), respectively. In the in silico mutagenicity and carcinogenicity investigations, all the compounds except TC exhibited mutagenicity. Among all the natural anti-tubercular agents only DNF and TC demonstrated carcinogenicity in both mouse and rat models. The AL and PG were carcinogenic only in mouse but in rat model they were noncarcinogenic. On the other hand, IA, BPG and PC were noncarcinogenic in both mouse and rat model. In addition, the risk of inhibition of human ether-a-go-go-related (hERG) gene was varied from low to medium risk. Our computed properties may be assistance for the development of promising candidates to combat M. tuberculosis with better pharmacokinetic and toxicological profile.
Keywords: Anti-tubercular agents,Virtual screening, Physicochemical properties, Pharmacokinetics, Toxicological properties.